Dielectrics for Terahertz Metasurfaces: Material Selection and Fabrication Techniques. Issue 3 (25th September 2019) - Ako, Rajour Tanyi; Upadhyay, Aditi; Withayachumnankul, Withawat; Bhaskaran, Madhu; Sriram, Sharath
Abstract: Manipulation of terahertz radiation opens new opportunities that underpin application areas in communication, security, material sensing, and characterization. Metasurfaces employed for terahertz manipulation of phase, amplitude, or polarization of terahertz waves have limitations in radiation efficiency which is attributed to losses in the materials constituting the devices. Metallic resonators‐based terahertz devices suffer from high ohmic losses, while dielectric substrates and spacers with high relative permittivity and loss tangent also reduce bandwidth and efficiency. To overcome these issues, a proper choice of low loss and low relative permittivity dielectric layers and substrates can improve field confinement and reduce dissipation. Alternatively, replacing metallic resonators with a moderate relative permittivity dielectric material that supports cavity mode resonances also reduces dissipation due to the absence of conduction current. Herein, an overview of dielectric materials employed as spacers and dielectric resonators is provided, and the fabrication methods employed to realize these devices at the terahertz frequency range are also presented. Material selection guidelines, material‐specific and application‐specific fabrication quality metrics are outlined, and new techniques are proposed. Abstract : Correct choice of dielectric materials can overcome low efficiency and low operational bandwidth in terahertz metasurface devices. A guide to their selection based on properties and fabrication compatibility is presented. State‐of‐the‐art examples of dielectrics demonstrated as spacers and substrates and as resonant structures are covered, highlighting that selection and handling of dielectric materials can determine the performance of terahertz devices.